Comunity Participation in Indonesia Development Policy: Neo-Liberal and Post-Marxism Prespective - Tubagus Furqon Sofhani (Journal of Regional and City Planning, 2005)
The meaning of community participation in Indonesian development history at New Era and Reformation has many been changed. The evolution of the meaning is the implication of the dynamic economic and political changing in Indonesia. It is also the consequence of its interaction with neo-liberal and post-Marxism that is promoted by international development institution and other development actors. Three phases movement of community participation meaning have been identified and analyzed in this paper on discussion in two-development paradigms: neo-liberalism and post-Marxism.Keywords: community participation, planning process; neo-liberalism, post-marxism